Faktor–Faktor yang Berhubungan dengan Kesehatan Mental Ibu Hamil di Wilayah Kerja Puskesmas Ciseeng Kabupaten Bogor Jawa Barat Tahun 2025 - Amabel Kyla Charity; Dwi Puji Astuti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Background: Mental health disorders in pregnant women reach 10,1% globally and are higher in developing countries (15.6% during pregnancy, 19.8% postpartum) according to the WHO. The prevalence in West Java increased from 8.1% (2013) to 10% (2018) according to Riskesdas. Mental health is important for pregnant women to know about because it can affect the well-being of both the mother and the fetus. Early and accurate detection is also necessary for mothers who are vulnerable to mental health issues. Objevtive: This study aims to identify the factors associated with the mental health of pregnant women in Puskesmas Ciseeng, Kabupaten Bogor, Jawa Barat in 2025.  Methods: This research is quantitative and analytical with cross-sectional approach. The population in this study consists of all pregnant women who attend antenatal care (ANC) visits, totaling 505 pregnant women at Puskesmas Ciseeng Kabupaten Bogor Jawa Barat in 2025, with a sample size of 84 pregnant women. The sampling technique used is consecutive sampling. The dependent variable is the mental health of pregnant women, while the independent variables are parity, economic status, husband's support, family support, and social environment. The characteristics of the respondents are age at the time of pregnancy and level of education. The research instrument used a questionnaire to determine support from husbands and families, and the SRQ-20 was used for mental health. The statistical test used is the chi-square test. Results: From the result of the research, there is relationship between the mental health of pregnant women with parity (p value= 0,007),  there is relationship between the mental health of pregnant women with economic status (p value= < 0,001), there is relationship between the mental health of pregnant women with husband’s support (p value= < 0,001), there is relationship between the mental health of pregnant women with family and social environment support (p value= <0,001). Conculsion: There is a relationship  between parity, economic status, husband’s support, family and social environment support with the mental health of pregnant women.